Pierre Bourdieu ve Spor Sosyolojisine Katkıları - Yüksel, Murat (Journal of History Culture and Art Research, 2019)
Pierre Bourdieu and Contributions to Sociology of Sport Abstract This study aims to introduce Pierre Bourdieu’s life, works, sociology, concepts he created and his contributions to the sociology of sports. The research was conducted with the literature search method. Bourdieu is one of the important sociologists of modern French sociology. His sociological point of view, qualified works and the theories/concepts he developed have carried him to the peak of intellectual life. In his academic life, subjects notably culture, education, art, politics, intellectuals, class, power, state, poverty, gender, economic-political, media and sociology of science, he has succeeded in enriching his sociology as a sociologist who has written many important works on many subjects and constantly creating new concepts and theories. The most striking feature of his sociology is to benefit from statistical methods and survey techniques. When Bourdieu’s works are examined, it is seen that none of these new concepts created contradicts the ones he has produced before, there is no change in his basic point of view or acceptance and he carried his own sociology further. Another importance of Bourdieu’s sociology is related to the in-depth analysis of the theories or concepts produced by empirical studies and demonstration of responses in practice. In addition, his sociology is a sociology that raises on the ideas of classical sociologists, avoids structure-individual dualism, combines theory and practice, and attempts to reveal the relationship between the social structure and the symbolic structure. The most important concepts of Bourdieu are habitus, field and capital. He tries to understand social hierarchy, domination relations and class differences through these concepts. It is seen that sports play an important role in the analysis of his theories or concepts. In general, it is important to monitor the fundamental dynamics of the field in the field of sport, to test the results of the habitus and capital differences directly in the sport, and also to show that the judgment or differences of taste appear as differences in sportive trends. Therefore, Bourdieu, both enabled the understanding of the social field and contributed to the development of sports sociology by making sociological analyzes on sports. Pierre Bourdieu ve Spor Sosyolojisine Katkıları Öz Bu çalışma Pierre Bourdieu’nün hayatını, eserlerini, sosyolojisini, ürettiği kavramları ve spor sosyolojine katkılarını tanıtmayı amaçlamaktadır. Araştırma literatür taraması yöntemiyle yapılmıştır. Bourdieu, çağdaş Fransız sosyolojisinin önemli sosyologlarından biridir. Sosyolojik bakışı, nitelikli eserleri ve geliştirdiği kuramlar/kavramlar onu entelektüel hayatın zirvesine taşımıştır. Akademik hayatında kültür, eğitim, sanat, siyaset, entelektüeller, sınıf, güç, devlet, sefalet, toplumsal cinsiyet, ekonomi-politik, medya ve bilim sosyolojisi gibi konular başta olmak üzere, daha birçok konuda oldukça önemli eserlere imza atan bir sosyolog olarak ve sürekli yeni kavramlar ve teoriler üreterek sosyolojisini zenginleştirmeyi başarmıştır. Onun sosyolojisinin dikkat çekici en temel özelliği, istatistiki yöntemlerden ve anket tekniğinden yararlanmaktır. Bourdieu’nün eserlerine bakıldığında, ürettiği bu yeni kavramların hiçbirisinin daha önce ürettikleri ile çelişmediği, temel bakış açısında ya da kabullerinde bir değişiklik olmadığı ve kendine özgü sosyolojisini daha ileri taşıdığı görülmektedir. Bourdieu sosyolojisinin bir diğer önemi, ürettiği kuram ya da kavramların ampirik çalışmalarla derinlemesine analizinin yapılarak, pratikte karşılıkların gösterilmesiyle ilişkilidir. Ayrıca, onun sosyolojisi, klasik sosyologların düşünceleri üzerinde yükselen, yapı-birey düalizminden uzak duran, teori ve pratiği bir araya getiren ve sosyal yapıyla sembolik yapı arasındaki ilişkileri açığa çıkarmaya çalışan bir sosyolojidir. Bourdieu’nün en önemli kavramlarının başında habitus, alan ve sermaye gelir. Bu kavramlar üzerinden, toplumsal hiyerarşiyi, tahakküm ilişkilerini ve sınıf farklılıklarını anlamaya çalışır. Onun kuram ya da kavramlarının analizinde sporun da önemli bir yer tuttuğu görülür. Genel olarak alanın temel dinamiklerini spor alanında da izlemek, habitusun ve sermaye farklılıklarının sonuçlarını doğrudan spor özelinde de test etmek ve aynı zamanda beğeni yargısının ya da farklılıklarının sportif eğilimlerdeki farklılıklar olarak da ortaya çıkması önemlidir. Dolayısıyla Bourdieu, spor üzerinden sosyolojik analizler yaparak, hem toplumsal alanın anlaşılmasına olanak sağlamış hem de spor sosyolojisinin gelişmesine katkı sunmuştur.